From structure topology to chemical composition. VIII. Titanium silicates : the crystal chemistry of mosandrite from type locality of Låven (Skådon), Langesundsfjorden, Larvik, Vestfold, Norway - E. Sokolova; F. Camara (Mineralogical Magazine, 2008)
The crystal structure of mosandrite, ideally Na2 Ca4REETi (Si2O7)2 OF3, a = 7.4184(8), b = 5.6789(6), c = 18.873(2) Å, β = 101.410(2)°, V = 779.35(5) Å3, space group P21/c, Z = 2, Dcalc = 3.363 g.cm-3, from the type locality, Låven (Skådön), Langesundsfjorden, Larvik, Vestfold, Norway, has been refined to R1 = 6.33% on the basis of 1113 unique reflections Fo 5 4sF . Electron microprobe analysis gave the empirical formula Na1.99 (Ca3.93 Sr0.02) ∑3.95 (Ce0.41 La0.16 Nd0.1 3Pr0.04 Sm0.02 Dy0.01 Y0.13) ∑0.90 (Ti0.864+ Nb0.08 Zr0.05) ∑0.99 (Si2 O7)2 (F1.20 O0.80) ∑2.00 F2, Z = 2, calculated on the basis of 18 (O + F) a.p.f.u. The crystal structure of mosandrite is a framework of TS (titanium silicate) blocks. The TS block consists of HOH sheets (H-heteropolyhedral, O-octahedral). The TS block in mosandrite exhibits linkage and stereochemistry typical for Group I (Ti = 1 a.p.f.u.) Ti-disilicate minerals: two H sheets connect to the O sheet such that two (Si2O7) groups link to the trans edges of a Na polyhedron of the O sheet. The O sheet cations give Na(NaCa)Ti (4 a.p.f.u.). The TS blocks link via common vertices of (Si2O7) groups and common vertices and edges of Ca-dominant MH and AP polyhedra. Two adjacent TS blocks are related by the glide plane cy. Composition and topology of the TS block in mosandrite and rinkite are identical. The crystal structure of mosandrite from the type locality is topologically and chemically identical to that of rinkite from the type locality of Kangerdluarssuk, Greenland.